Campanian (Late Cretaceous) ammonites from the Bergstrom Formation in Central Texas - Kennedy, W; Cobban, W (1999)
Calcareous concretions 12-18 m below the top of the Upper Cretaceous Bergstrom Formation in Travis County, Texas, contain abundant ammonites. Menuites stephensoni YOUNG, 1963, Manambolites ricensis YOUNG, 1963, and Trachyscaphites pulcherrimus (ROEMER 1841) have been described previously but are minor elements of the fauna, which is characterized, in addition, by abundant Didymoceras binodosum (KENNEDY and COBBAN 1993a) and Spiroxybeloceras kimbroense gen. and sp. n., with rarer Menuites sp., Placenticeras sp., and Baculites texanus sp. n. The fauna correlates with the Baculites scotti zone (Campanian) in the U.S. Western Interior and part of the Bostrychoceras polyplocum zone in northwestern Europe.